2008
DOI: 10.1007/978-1-59745-273-1_4
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Fertilization With Isolated Higher Plant Gametes

Abstract: Methods have been developed to isolate gametes of higher plants and to fertilize them in vitro. Zygotes, embryos, fertile plants and endosperm can now be obtained from in vitro fusion of pairs of sperm and egg cells and of pairs of sperm and central cells, respectively. This allows examination of the earliest developmental processes precisely timed after fertilization. The isolated egg and central cell, fertilized and cultured in vitro, are able to self-organize apart from each other and without mother tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…One of the first technological breakthroughs was the establishment of a protocol that allows manual isolation of individual FG cells (Kranz and Dresselhaus, 1996). The method involves partial digestion of the cellular matrix by cell-wall-degrading enzymes, which, however, has the potential to affect the transcriptional landscape of the isolated cells (Dresselhaus et al, 1994;Wei and Sun, 2002).…”
Section: Transcriptome Profiling Of Fg Cellsmentioning
confidence: 99%
“…One of the first technological breakthroughs was the establishment of a protocol that allows manual isolation of individual FG cells (Kranz and Dresselhaus, 1996). The method involves partial digestion of the cellular matrix by cell-wall-degrading enzymes, which, however, has the potential to affect the transcriptional landscape of the isolated cells (Dresselhaus et al, 1994;Wei and Sun, 2002).…”
Section: Transcriptome Profiling Of Fg Cellsmentioning
confidence: 99%
“…Although the success has so far been confi ned in achieving fertilization and embryo development between gametes of compatible species, studies of Kranz and his associates (Kranz 1997(Kranz , 2008Scholten and Kranz 2001 ) have shown that there is no technical diffi culty in achieving in vitro fertilization between isolated egg and sperm cells in interspecifi c and intergeneric combinations. However, the development of zygotes is restricted to crosses between closely related species (Kranz and Dresselhaus 1996 ). Hybrid zygotes between maize (egg donor) and sperm cell of many other members of Poaceae gave rise to multicellular structures, while those resulting from the egg of maize and sperm of a distant species, Brassica , failed to divide.…”
Section: In Vitro Fertilizationmentioning
confidence: 98%
“…Subsequently the sperm cell was also fused with the central cell; the fusion product did not give rise to the embryo but gave rise to an unorganized tissue comparable to the endosperm in vivo. Subsequently several modifi cations in the protocols to improve the effi cacy of fusion and embryo development have been reported (Kranz 1997 ;Wang et al 2006 ;Kranz et al 2008 ).…”
Section: In Vitro Fertilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunocytochemical analysis was performed according to the protocol described by Hoshino et al (2004) and Kranz et al (2008) A Nikon TE2000-E inverted microscope equipped with a Nikon C1Si spectral imaging confocal laser scanning system (Nikon Co. Ltd., Tokyo, Japan) was used for confocal microscopy experiments, and the data analyzed using the Nikon EZ-C1 3. …”
Section: Immunofluorescence Analysis For Microtubule Detectionmentioning
confidence: 99%